3D printing of bioactive macro/microporous continuous carbon fibre reinforced hydroxyapatite composite scaffolds with synchronously enhanced strength and toughness. Issue 10 (August 2022) - Zhao, Xueni; Liu, Ao; Zhou, Lian; Yang, Zhi; Wei, Sensen; Zhao, Zhenyang; Fan, Qiang; Ma, Linlin
Abstract: Continuous carbon fibre (CF) reinforced HA (CF/HA) composite scaffolds were prepared using a self-designed and manufactured 3D printer. The optimised design of nozzle structure and the tailored viscoelastic property of HA inks ensured compound extrusion of monofilament and multifilament CF with HA rod. The composite scaffolds designed using the CAD programme and sintered via a suitable process exhibited a hierarchical macro/microporous structure and contained approximately 50% HA and 50% β-TCP. The continuous CF synchronously enhanced the strength and toughness of the scaffolds. The compressive strengths of 1CF/HA and 5CF/HA were 11.4 ± 1.7 MPa and 16.3 ± 2.6 MPa, respectively, which were approximately double and triple compared with that of HA scaffolds. The fracture toughness of 1CF/HA was approximately double that of HA scaffolds and close to that of cortical bone. In vitro and in vivo studies demonstrated that 1CF/HA also had apatite formation capability and adequate bone regeneration capacity. Graphical Abstract: ga1